Investigating the Relationship between Attachment Styles and Academic Burnout: The Mediating Role of Alexithymia - Zahra Amanat; Majid Barzegar; Azarmidokht Rezaei; Hossein Bagholi (Iranian Journal of Educational Research)
Objective: The objective of the current investigation is to explore the social cognitive precursors of academic burnout within a causal model mediated by alexithymia. Methods: The methodology employed in this study consists of correlation and structural equation modeling. The target population comprised all high school students in the 2021 of Firozabad city, with a sample size of 285 individuals selected through multi-stage cluster random sampling. Data collection involved the utilization of Bresso et al.'s academic burnout scale, Bagby et al.'s alexithymia scale, and Collins and Reed's attachment styles scale. The data analysis was conducted using structural equation modeling, with the mediation role being examined through the application of the bootstrap in AMOS. Results: The results indicated that attachment styles exhibited a direct impact on alexithymia and an indirect influence mediated by alexithymia on academic burnout. Moreover, alexithymia demonstrated a direct association with academic burnout. Conclusions: Consequently, it is plausible to assert that attachment styles and alexithymia constitute pivotal constructs in elucidating academic burnout.